Entre livros e games : jogando com Alice no País das Maravilhas - Santiago, Rejania Francisca da Cruz (2020)
Between books and games: playing with Alice in Wonderland this is a research about double engagement of gamer-reader in adaptation as adaptation (HUTCHEON, 2011). In the context of digital literature or cyberliterature, this gamer-reader or player's profile plays video games and reads books, therefore our research corpus are the videogames American McGee's Alice (2000) and Alice: Madness Returns (2011), that was transcoded from the books Alice in Wonderland and Alice Through the Looking Glass (CARROLL, 2018). And our research question is: “How the gamer-reader reads an adaptation from Alice’s histories?”, whereas these games setting book's people in motion (REIS, 2016), that is, characters from our experiences with literature classics. In this sense, I first reflect on video games in literature and their circulation modes in the social sphere, taking adaptation as a point of cultural convergence (JENKINS, 2013). Therefore, I discuss questions that are own of transcoded video games regarding the art of storytelling. And finally, I analyze my gameplay moving through the articulated complexity of this dissertation, I reflect: on the types of gamer-reader engagement, the nature of storytelling and the path that make the character Alice, a living text in gamers- readers's imagination and literary productions.